O currículo escolar: uma análise na perspectiva da inclusão de alunos com deficiência intelectual - Oliveira, Erika Soares de (2011)
A mid the many transformations and advances that the contemporary society is going through, the right to education is a topic that does not end and becomes increasingly present, given the urgency of including students with disabilities in education. Given this new reality, schools are challenged to receive them with quality, and implement actions that promote favorable conditions for their development at school. Accordingly, it is fundamental the organizational restructuring of education to meet the specific needs of students. Thus, it is imperative that educational institutions defining the type of person who intend to form and the society proposing to build. These are aspects that precede any question, since the knowledge covered in the curriculum will contribute directly to the creation of human beings are involved there. Based on this theme, this assignment reports aspects of a survey of a local public school, located in Natal/RN, which deals with the analysis of the curriculum and its implementation in teaching practice in the classroom, before the inclusion of students with disabilities intellectual. Thus, to undertake a study of case with five professionals at school, involving documentary analysis and observation of the curriculum of the pedagogical practice of teachers in the classroom, as well as conducting an interview with all stakeholders. To this end, the data analyzed shows that, although the right of citizens with disabilities is guaranteed by constitutional law, the school, locus of this study, have not realized the extent of conquest. Does not recognize the fact of being in school and learn together with others is also a right of persons with disabilities. Thus, while your resume is to present a progressive vision, believed to be open, concerned with the selection and organization of content, with flexibility in defining the goals, with the search for diversification of the procedures adopted, as well as the planning activities teaching and learning based on the level of student learning, this is not effective in teaching practice, either through ignorance of the guidelines defined either by lack of knowledge about the proposal and an inclusive curriculum can provide answers to all educational students, including those with intellectual disability